PERANCANGAN BUKU FOTOGRAFI ESAI “TREATS AND TEMPTATIONS” TENTANG KUE PASTRY UNTUK MENINGKATKAN MINAT MASYARAKAT DI KOTA MALANG TERHADAP KUE PASTRY - Billina, Aulia Salsa; Nugroho, Didit Prasetyo; Nirwana, Aditya (Ma Chung Press, Universitas Ma Chung, 2025)
Malang City has the potential to support economic growth through adequate infrastructure for industry, tourism, education and dynamic culinary delights. Pastry trend is one of an iconic public craze in Malang City, so many cafes or bakeries sell various pastry variants in Malang City especially for those who worls as a food photography. However, there is a lack of promotion at cafes or bakeries in Malang City that provide pastry variant menus, which has an impact on potential public interest. Therefore, media informatin is needed to helps people who are interest in visiting cafes that provide pastry variants with good taste and attractive visuals, through a design that aims to get a visualization of the concept through the media of a photography essay book contains of an information about cafe pastry in town. The design methods used are qualitative data collection methods and creative communication design methods. This photography essay book contains information about pastry also the photos of pastry food, with a book size of 20 x 20 cm with a total of 128 pages, full color, bound, and using a hardcover. The conclusion of this design is to obtain a visualization of the concept of a photography essay book to provide information about pastry through photo visualization accompanied by narration through books and supporting media such as notepads, tote bags, keychains, tumblers, stickers and postcards.